Job Demands and Recovery Experience: The Mediation Role of Heavy Work Investment - Julio César Acosta-Prado; Juan Guillermo Sandoval-Reyes; Carlos Sanchís-Pedregosa (Amfiteatru Economic)
The evolving labor market is increasingly competitive and more demanding for most occupations and especially pertinent to health professionals investing many resources to provide excellent care service. However, the nature of the external factors, such as organizational culture and workload, seemed to be related to heavy work investments (HWI) and health outcomes, such as recovery experiences. This study aims to explore among Colombian health professionals, the effect of job demands (JD) on recovery experience (RE), mediated by HWI. The proposed model was assessed through Partial Least Squares Structural Equation Modelling (PLS-SEM) and an importance-performance map analysis was performed to expand the initial results. Results support the stated hypotheses regarding direct and indirect effects among JD, RE and HWI. This study contributes to understanding job demands within the health sector. Moreover, it pinpoints opportunities to foster adequate management of work investment and recovery experiences that protect well-being while maintaining a quality care service.